Editorial - Hashim, Hilwati (Journal Of Cardiovascular, Neurovascular & Stroke, 2020)
WELCOME to our 2nd issue of the inaugural volume of Journal of Cardiovascular, Neurovascular, and Stroke (CVNS). With thousands of journals available worldwide, why do we need another one? In this competitive era of publications driven by advancements in research, particularly in the medical field, scientists and clinicians continually strive to publish their research findings. Authors, and particularly those from South East Asian countries, may find it difficult to publish their papers in the more established European or American journals. Thus, we felt that there was a need to provide such a platform for these authors to showcase and share their research. Furthermore, many of the established journals are no longer accepting case reports, yet there is always something to be learned from anecdotal case studies. This journal provides a venue for case reports to be published. We cannot ignore the COVID-19 pandemic that is currently raging throughout the world. It may affect our readers differently. Some of you may be confined to your homes and some may still be able to continue with daily life, albeit with limitations. In terms of research and publications, some may find that their research activities are limited or even completely halted. However, others may choose to use this period of relative inactivity to catch up on their writing, reviews, and publications or merely catch up on the latest findings in medical sciences. Research grants, particularly related to COVID-19, are still being offered and new papers are still being published. The editorial committee members of this journal remain committed to reviewing and publishing submissions in a timely manner. We welcome all submissions related to Cardiovascular, Neurovascular and Stroke and will do our best to expeditiously process them through our peer review system . Our hope is that everyone will stay safe during this trying period. Take care. Thank you. Hilwati Hashim CVNS Editor-in-Chief